2017
DOI: 10.21010/ajtcam.v14i3.8
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Bursera Morelensis Ramírez Essential Oil

Abstract: Background: Bursera morelensis, known as "Aceitillo", is an endemic tree of Mexico. Infusions made from the bark of this species have been used for the treatment of skin infections and for their wound healing properties. In this work, we present the results of a phytochemical and antimicrobial investigation of the essential oil of B. morelensis. Materials and Methods:The essential oil was obtained by a steam distillation method and analyzed using GC-MS. The antibacterial and antifungal activities were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Since this time the development of antifungals against C. albicans always has been a priority for the scientific community. However, the prolonged management of candidiasis using antifungals might cause the development of drug-resistant candidiasis [ 12 , 13 , 14 ]. An alternative has involved the search for new treatments in medicinal plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this time the development of antifungals against C. albicans always has been a priority for the scientific community. However, the prolonged management of candidiasis using antifungals might cause the development of drug-resistant candidiasis [ 12 , 13 , 14 ]. An alternative has involved the search for new treatments in medicinal plants.…”
Section: Discussionmentioning
confidence: 99%
“…The Cañada Region located in the Mexican State of Oaxaca, has a great variety of endemics plant which are commonly used in traditional medicine [ 12 ]. Bursera morelensis Ramírez belongs to the Burseraceae family, which has been used for preparing resin and bark infusions for the treatment of skin wounds [ 13 , 14 ], addition to alleviate diverse pains and bruises [ 15 ]. The aim of this study was to evaluate the anti- Candida activity of the essential oil extracted from B. morelensis and compare the activity of two present compounds in the essential oil.…”
Section: Introductionmentioning
confidence: 99%
“…F. monilifome (IC50: 2.27 mg/mL) was the most sensitive fungal strain. This work provided scientific evidence for the antimicrobial activity of the B. morelensis [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antibacterial mechanism of polyphenols may be related to their ability to deactivate enzymes of crucial importance for bacterial survival, towards to form complexes with proteins through hydrogen bonds with consequently formation of quinone, probable targets for quinone bindings on the bacterial cell are proteins of cell envelope and cell wall, surface-exposed adhesins and membrane-bound enzymes (Brudzynski & Maldonado-Alvarez 2015). It has been reported the use of B. simaruba bark for skin infections, as well as antibacterial, antifungal and cytotoxic activities (Canales-Martínez et al 2017). The results indicate the existence of antibacterial compounds in the hydroalcoholic extracts of species studied (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the antioxidant properties of the essential oil from B. graveolens may be associated with its main constituents, limonene (34.9 %) and α-terpineol (13.4 %) which are terpenes (Fon-Fay et al 2019). Furthermore, it has been demonstrated that the essential oil of B. morelensis includes terpenes, which contribute to its antimicrobial activity (Canales-Martínez et al 2017).…”
mentioning
confidence: 99%